Inhibition of TRPM8 Channels Reduces Pain in the Cold Pressor Test in Humans - Winchester, Wendy J.; Gore, Katrina; Glatt, Sophie; Petit, Wendy; Gardiner, Jennifer C.; Conlon, Kelly; Postlethwaite, Michael; Saintot, Pierre-Philippe; Roberts, Sonia; Gosset, James R.; Matsuura, Tomomi; Andrews, Mark D.; et al. (The Journal of pharmacology and experimental therapeutics, 2014)
The transient receptor potential (subfamily M, member 8; TRPM8) is a nonselective cation channel localized in primary sensory neurons, and is a candidate for cold thermosensing, mediation of cold pain, and bladder overactivity. Studies with TRPM8 knockout mice and selective TRPM8 channel blockers demonstrate a lack of cold sensitivity and reduced cold pain in various rodent models. Furthermore, TRPM8 blockers significantly lower body temperature. We have identified a moderately potent (IC50 = 103 nM), selective TRPM8 antagonist, PF-05105679 [(R)-3-[(1-(4-fluorophenyl)ethyl)(quinolin-3-ylcarbonyl)amino]methylbenzoic acid]. It demonstrated activity in vivo in the guinea pig bladder ice water and menthol challenge tests with an IC50 of 200 nM and reduced core body temperature in the rat (at concentrations >1219 nM). PF-05105679 was suitable for acute administration to humans and was evaluated for effects on core body temperature and experimentally induced cold pain, using the cold pressor test. Unbound plasma concentrations greater than the IC50 were achieved with 600- and 900-mg doses. The compound displayed a significant inhibition of pain in the cold pressor test, with efficacy equivalent to oxycodone (20 mg) at 1.5 hours postdose. No effect on core body temperature was observed. An unexpected adverse event (hot feeling) was reported, predominantly periorally, in 23 and 36% of volunteers (600- and 900-mg dose, respectively), which in two volunteers was nontolerable. In conclusion, this study supports a role for TRPM8 in acute cold pain signaling at doses that do not cause hypothermia.